Formulation of Levocetirizine-Loaded Core-Shell Type Nanofibrous Orally Dissolving Webs as a Potential Alternative for Immediate Release Dosage Forms - Adrienn Kazsoki; Barnabás Palcsó; Safaa Mohammed Omer; Zoltan Kovacs; Romána Zelkó (MDPI AG, 2022)
Several applications of nanofiber-based systems are based on their corresponding functionality-related properties, which often cannot be satisfied by a fiber web with a monolithic structure because of the various physicochemical properties and amounts of embedded compounds. Therefore, one of the main directions in the development of fiber systems is creating core-shell type complex fiber structures that can provide application-specific properties to the fiber matrix. The present study aimed to formulate levocetirizine-loaded core-shell type hydrophilic polymer-based fibrous systems. The core phase contained the antihistamine levocetirizine, while the permeation enhancer (Na-taurocholate), the local pH regulator (citric acid), and the cyclodextrin used as a taste masking agent were included in the shell phase of the fibrous formulation. Scanning electron microscopy images indicated that a randomly oriented homogeneous fibrous structure was obtained, while the Raman mapping and chemometric analysis confirmed the partially formed core-shell structure. A fast release rate of the antihistamine drug from the complex structural fibrous system was obtained (within 1 min complete dissolution can be observed) due to its increased surface area to volume ratio and its more favorable wettability properties, which consequently allows for more erosion. The masking properties against the unpleasant bitter taste of API of the formulated complex nanostructure were confirmed by the results of the electronic tongue. The formulated complex nanostructure enabled fast and complete release of the API, providing a potential enhancement in the rate and extent of absorption while masking the unpleasant taste of levocetirizine, which has a high impact on the patient adherence. All in all, the results show that the developed orally dissolving fibrous web formulation can be a potential alternative to the commercially available orally disintegrating tablets.